IMT and VO2max analysis on junior athletes, futsal and football branches: Literature Scopus - Purba, R. H.; Susanti, S. A. (Journal of Human Sport & Exercise, 2021)
State University of Jakarta students, especially the Faculty of Sports Science, consist of athletes in their respective sports, they are required to have various physical abilities or movement skills and master the techniques of these sports, as well as being able to apply them in competitions or sports competitions that they participate in, as well as are required to have achievements in the sport they do. To get an achievement, athletes must have excellent physical fitness and be supported by ideal body proportions and have high enthusiasm and motivation. This study aims to determine the condition of IMT (BMI) and VO2max male junior athletes in Futsal and soccer sports at State University of Jakarta. This type of research is quantitative research using survey techniques with the method used is descriptive. The results of this study are it can be said that the IMT condition of male junior athletes in futsal and soccer at State University of Jakarta is underweight category as much as 10% or 5 athletes, normal category is 64% or 32 athletes, overweight category is 12% or 6 athletes, and obesity category as much as 14% or 7 athletes. Meanwhile, the results of the calculation of the percentage of VO2max data for male junior athletes in futsal and soccer at State University of Jakarta are 12% or 6 athletes, either 18% or 9 athletes, 44% or 22 athletes, enough categories and the less category was 26% or 13 athletes, while the lacking category was not included in the category.